2009
DOI: 10.1016/j.bcp.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major human hepatic and placental enzymes responsible for the biotransformation of glyburide

Abstract: One of the factors affecting the pharmacokinetics (PK) of a drug during pregnancy is the activity of hepatic and placental metabolizing enzymes. Recently, we reported on the biotransformation of glyburide by human hepatic and placental microsomes to six metabolites that are structurally identical between the two tissues. Two of the metabolites, 4-trans- (M1) and 3-cis-hydroxycyclohexyl glyburide (M2b), were previously identified in plasma and urine of patients treated with glyburide and are pharmacologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 37 publications
6
46
3
Order By: Relevance
“…These clinical studies appear to suggest that CYP2C9 contributes significantly to glyburide metabolism in vivo. On the other hand, in vitro studies using human liver microsomes have shown that CYP3A4 contributes greater than 50% of glyburide metabolism, while CYP2C9 contributes a much smaller percentage (Naritomi et al, 2004;Zharikova et al, 2009;Zhou et al, 2010a). Additionally, Lilja et al showed that oral administration of clarithromycin, an inhibitor of CYP3A but not CYP2C9, significantly increased C max and the plasma AUC of glyburide (Lilja et al, 2007).…”
Section: Glyburide and Its Clinical Pharmacokineticsmentioning
confidence: 99%
See 4 more Smart Citations
“…These clinical studies appear to suggest that CYP2C9 contributes significantly to glyburide metabolism in vivo. On the other hand, in vitro studies using human liver microsomes have shown that CYP3A4 contributes greater than 50% of glyburide metabolism, while CYP2C9 contributes a much smaller percentage (Naritomi et al, 2004;Zharikova et al, 2009;Zhou et al, 2010a). Additionally, Lilja et al showed that oral administration of clarithromycin, an inhibitor of CYP3A but not CYP2C9, significantly increased C max and the plasma AUC of glyburide (Lilja et al, 2007).…”
Section: Glyburide and Its Clinical Pharmacokineticsmentioning
confidence: 99%
“…It is possible that glyburide is metabolized in vivo through the joint actions of hepatic CYP3A and CYP2C9. In vitro metabolism studies using human liver microsomes or recombinant systems revealed that, besides CYP3A4 and CYP2C9, glyburide was also metabolized by other cytochrome P450 enzymes such as CYP3A5, CYP2C8 and CYP2C19, but to a much lesser extent (Naritomi et al, 2004;Zharikova et al, 2009;Zhou et al, 2010a). Zharikova et al determined five metabolites of glyburide formed in human liver microsomes: M1 (4-transhydrocyclohexyl glyburide), M2a (4-cis-hydrocyclohexyl glyburide), M2b (3-cishydrocyclohexyl glyburide), M3 (3-trans-hydrocyclohexyl glyburide), M4 (2-transhydrocyclohexyl glyburide) and M5 (ethylene-hydroxylated glyburide) (Zharikova et al, 2009;Zharikova et al, 2007).…”
Section: Glyburide and Its Clinical Pharmacokineticsmentioning
confidence: 99%
See 3 more Smart Citations